Table of Content - - (Journal of Islamic Sciences, 2023)
Table of Content:1. The spread of the phenomenon of atheism and ways to resist itDr. Abdulhameed Abdo Mohsen Allaw2. The relationships between Fatimah, the daughter of prophet Mohammed peace be upon him,  and Abu Baker and Omar, may God be pleased with them allDr. Hadi Qaed Alhabardi3. Protecting family members from the inside according to Quranic middle approachDr. Naif Nasser Almansour4. Women's Issues in Liberal Thought "The Verses of Inheritance as a Model"Mrs. Mona Saud Al-Mutairi5. Sarfa as one of the miraculous aspects of The Quran between the supporters and opponents, review and studyDr. Shahd Atwan Saleh Al-Maliki
Keywords: Journal of Islamic Sciences